2017
DOI: 10.36076/ppj.2017.318
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pain Processing Between Patients with Chronic Low Back Pain, Recurrent Low Back Pain, and Fibromyalgia

Abstract: Background: The impairment in musculoskeletal structures in patients with low back pain (LBP) is often disproportionate to their complaint. Therefore, the need arises for exploration of alternative mechanisms contributing to the origin and maintenance of non-specific LBP. The recent focus has been on central nervous system phenomena in LBP and the pathophysiological mechanisms underlying the various symptoms and characteristics of chronic pain. Knowledge concerning changes in pain processing in LBP remains amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…In our sample, a clinically feasible measure of pain sensitivity (pressure-pain threshold) did not diferentiate patients with LBP with NPP from patients without a NPP. Tis result is inconsistent with prior literature demonstrating patients with fbromyalgia display elevated thermal and pressure sensitivity compared to healthy controls [60,67]. Patients with LBP and fbromyalgia have heightened pain sensitivity measured with pressure-pain threshold [19].…”
Section: Characteristics Of Patients With Lbp Presenting With Nppcontrasting
confidence: 78%
“…In our sample, a clinically feasible measure of pain sensitivity (pressure-pain threshold) did not diferentiate patients with LBP with NPP from patients without a NPP. Tis result is inconsistent with prior literature demonstrating patients with fbromyalgia display elevated thermal and pressure sensitivity compared to healthy controls [60,67]. Patients with LBP and fbromyalgia have heightened pain sensitivity measured with pressure-pain threshold [19].…”
Section: Characteristics Of Patients With Lbp Presenting With Nppcontrasting
confidence: 78%
“…In contrast, no QST profile is specific to a given clinical pain condition ( 204 ). In addition, studies using QST to differentiate pain patients from healthy controls ( 205 , 206 ) or using QST for prognostic profiling of pain patients ( 207 ) are still conflicting. Recent data has also shown that chronic pain and disability can be reduced with no associated change in QST profiles ( 208 ), and QST profiles can improve with treatment without a significant change in spontaneous subjective clinical pain ( 196 ).…”
Section: Comparison To Other Pain (Bio-) Markersmentioning
confidence: 99%
“…The estimated prevalence of FM is approximately 2.7% in the general population, with the highest rates observed in the USA and Turkey 3. Despite ongoing scientific debate on the pathophysiology of FM, it is generally considered a central sensitisation syndrome with a biopsychosocial aetiology 2 4…”
Section: Introductionmentioning
confidence: 99%